The BLOODSAFE program: Building the future of access to safe blood in Sub‐Saharan Africa. Issue 11 (29th September 2022) - Delaney, Meghan; Telke, Susan; Zou, Shimian; Williams, Makeda J.; Aridi, Jackline O.; Rudd, Kristina E.; Puyana, Juan Carlos; Kumar, Pratap; Appiah, Bernard; Dei‐Adomakoh, Yvonne; Asamoah‐Akuoko, Lucy; Olayemi, Edeghonghon; et al.
Abstract: Background: The supply of blood in many low‐ and middle‐income nations in Sub‐Saharan Africa (SSA) does not meet the patient care needs. Lack and delay of blood transfusion cause harm to patients and slow the rate of progress in other parts of the health system. Recognizing the power of implementation science, the BLOODSAFE Program was initiated which supports three SSA research study teams and one data coordinating center (DCC) with the goal to improve access to safe blood transfusion in SSA. Study Design and Methods: The study team in Ghana is focusing on studying and decreasing iron deficiency in blood donors and evaluating social engagement of blood donors through different approaches. The study team in Kenya is building a "vein to vein" workflow model to elucidate and devise strategies to overcome barriers to blood donation and improve infrastructural components of blood product production and use. The Malawi team is studying the infectious disease ramifications of blood donation as well as blood donor retention strategies aimed at blood donors who commence their donation career in secondary schools. Results and Discussion: Together the project teams and the DCC work as a consortium to support each other through a shared study protocol that will study donor motivations, outcomes, and adverse events across all three countries. The BLOODSAFE Program has the potential to lead to generalizable improvement approaches for increasing access to safe blood in SSA as well as mentoring and building the research capacity and careers of many investigators.